Knowledge, attitude and perception of patients towards informed consent in obstetric surgical procedures at Aminu Kano Teaching Hospital - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background/Aim:The practice of informed consent prior to any surgical procedure should form the fundamental element that serves to protect both patient and surgeon from prosecution. The aim of this study was to assess knowledge, attitude and perception of women towards informed consent prior to Surgery in Obstetrics and Gynaecology department of Aminu Kano Teaching Hospital.Materials and Methods:This was a cross-sectional study conducted among 398 women who had undergone surgery at the Obstetrics and Gynecology department of the Aminu Kano Teaching Hospital, Kano State, Nigeria. Data was obtained following surgery but prior to discharge and was analyzed using SPSS version 17.Results:Three hundred and ninety eight women were recruited. The mean age was 30.3 years ± 5.2. All respondents believed signing a consent prior to surgery was important and believed it was a legal document involved in decision making process. Ninety seven percent of the respondents were satisfied with the explanation given to them prior to the surgery however, 15.8% had some reservations to the explanations while 3% were not completely satisfied with the explanations.Conclusion:Awareness and knowledge of consent was high in this study and the respondents had positive attitude towards signing consent.